2007
DOI: 10.1016/j.ijpharm.2007.02.033
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid nanodisks

Abstract: Nanodisks are nanoscale, disk-shaped phospholipid bilayers whose edge is stabilized by association of apolipoprotein molecules. Self assembled ND particles enriched with all-trans-retinoic acid (ATRA) [phospholipid:ATRA molar ratio = 5.5:1] were generated wherein all reaction components were solubilized. ATRA-ND migrated as a single band (Stokes' diameter ∼20 nm) on native gradient polyacrylamide gel electrophoresis. ATRA, phospholipid and apolipoprotein co-eluted from a Sepharose 6B gel filtration column, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…Hwang and coworkers found that ATRA loaded in a phospholipid-based microemulsion provided similar growth inhibitory effects on HL-60 and MCF-7 cell lines to that free ATRA (12). The result is also in agreement with a previous study showing that ATRA incorporated into Nanodisks, disk-shaped phospholipid bilayers whose edge is stabilized by the association of apolipoprotein molecules, mediated time-dependent inhibition of cultured HepG2 cell growth more effectively than free ATRA (27). Cancers associated with defects in the retinoic acid pathway respond well to ATRA therapy.…”
Section: In Vitro Release Of Atra-loaded Nlcssupporting
confidence: 92%
“…Hwang and coworkers found that ATRA loaded in a phospholipid-based microemulsion provided similar growth inhibitory effects on HL-60 and MCF-7 cell lines to that free ATRA (12). The result is also in agreement with a previous study showing that ATRA incorporated into Nanodisks, disk-shaped phospholipid bilayers whose edge is stabilized by the association of apolipoprotein molecules, mediated time-dependent inhibition of cultured HepG2 cell growth more effectively than free ATRA (27). Cancers associated with defects in the retinoic acid pathway respond well to ATRA therapy.…”
Section: In Vitro Release Of Atra-loaded Nlcssupporting
confidence: 92%
“…Ryan et al (7,8) synthesized nanodisk (ND) particles comprised of a disk-shaped phospholipid bilayer. The perimeter of the bilayer is stabilized by apoplipoprotein A1 molecules.…”
Section: Nanodisks -Drug Delivery Nanoparticle Vehiclesmentioning
confidence: 99%
“…This water insoluble bioactive lipid was stably incorporated into nanoscale lipid particles -the NDs (15,16). We hypothesized that, following cellular uptake and/or liberation of ATRA from ND, this retinoid would interact with intracellular binding proteins and, ultimately, nuclear hormone receptors, leading to target gene transactivation, cell growth arrest and/or apoptosis.…”
Section: Nanodisks -Drug Delivery Nanoparticle Vehiclesmentioning
confidence: 99%
“…[21][22][23][24] After equal moles of paclitaxel and POPC were mixed together in the presence of 100 mM sodium cholate, the detergent was removed either by dilution or dialysis and apolipoprotein A-I was added at the time of dilution or dialysis. After removing protein and paclitaxel precipitates by centrifugation, the supernatant was subjected to separation by size exclusion chromatography.…”
Section: Assembly Of Paclitaxel Nanoparticlesmentioning
confidence: 99%